Design And Development Of Programming Learning Platform Based On Heuristic Approach In Live Code Module With Iterative And Incremental Method(case Study: Information System Telkom University) - Ekky Novriza Alam; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract —Students of computer science in the world have the same problem of learning basic programming. Many of students difficulties in solving the different problems with the same algorithm solution. Students may easier to understand the syntax and intent of the statement coding programming language, however to apply them in the correct program code is difficult. The effectiveness method of learning introductory programming is live code method. In this research discussed on the development of live code method in programming learning platform based on heuristic approach that called CIDEC Platform as a solution to help student learn programming easier. This platform can help lecturer to make a live code question with own perspective and student can answer question with live code feature without install anything. For platform development, it used iterative and incremental method made in four iteration by involving business modelling, requirement analysis, analysis and design, implementation, and testing. Platform based web application is built with by using concept Model-View-Template (MVT) which utilize Python programming language within Django Framework and MySQL database. The live code compiler built with by using Java Development Kit and Ace Editor. The result of research is Live Code Module in Programming Learning Platform. For further research, focus development can develop by upgrade the case sensitive, add a type of question livecode can compile or shown to student and free live code area. So, lecturer can make a diverse questions of livecode,such as compare method,check the logic and check a return type. Student can do coding without specific course.